Research on legal aspects of digital rights, privacy, and ethical issues in the online environment - Sukhanov, Maksym; Kmetyk-Podubinska, Khrystyna; Khromov, Anatolii; Vovk, Mariia; Ostafiichuk, Liudmyla (My University, 2024)
As scientific advancements continue, the emergence of new computer programs and smartphones has led to the establishment of digital states on a global scale. A crucial imperative, necessitating meticulous consideration and legal codification, is the reservation of digital rights and privacy. Individual private rights must remain inviolate, necessitating the refinement of legislative activities in each state. This condition holds significant relevance and urgency, demanding careful consideration by legislators and effective implementation at the state level. The primary aim of this article is to undertake a comprehensive analysis and theoretical-legal exploration of the legal facets concerning digital rights privacy and ethical dilemmas within the online environment. A theoretical examination of the legal dimensions surrounding digital rights privacy, coupled with an in-depth investigation into ethical considerations within the online environment, enables the identification of lacunae in rulemaking processes and facilitates the proposition of remedial measures. Through an exhaustive analysis of the national and international legal and theoretical foundations, the author advocates for continued exploration and knowledge exchange among legislators regarding the regulation of digital rights privacy and the formulation of strategies to address ethical challenges. Within the course of this study, the author discerned and endorsed the proposal to implement a digital code. This realm of investigation necessitates ongoing scrutiny, modernization, and the practical implementation of favorable aspects, thereby offering resolutions to problematic issues. A proposition is set forth to enhance legal consciousness and awareness through the incorporation of ethics courses within the online environment, targeting the workforce, young individuals, and students by integrating such courses into the curriculum. The rationale behind this proposal lies in the belief that such an initiative would contribute to resolving issues related to integrity and ethical conduct in online communication. In recognition of the dynamic nature of science and technological advancements, lawmakers must evolve legal norms that account for all associated risks and gaps in the regulatory landscape.
Дослідження правових аспектів цифрових прав, приватності та етичних проблем в онлайн-середовищі
Keywords: computerization; digitalization; digital rights; ethical issues; online environment; privacy; scientific progress; theoretical and legal research; digital thing